Islamic Boarding School Culture and Character Education at Pondok Khalaf"Study at Minhajul Haq Purwakarta Boarding School" - Harsing Harsing; Isrun Abdurahman; Irfan Alkhotiri (Al Musa’adah : Journal of Community Service STAI Minhajul Haq, 2026)
Islamic boarding school culture is a system of values and social practices that has been formed through a long process since the early days of the spread of Islam in the archipelago. This system is not only a tradition, but also serves as an effective moral education tool for students. This study aims to examine how the culture of the pesantren at the Minhajul Haq Islamic Boarding School, as part of the khalaf pesantren, plays an important role in the formation of the character of the students. The research method uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the habituation of worship, strengthening manners, discipline, social interaction, and the integration of formal and non-formal education are important elements in the formation of the character of students. This research confirms that the pesantren culture in Minhajul Haq is an effective and relevant character education model in the modern context.